تطبيقات الذكاء الاصطناعي و تأثيرها على التسويق الإلكتروني-دراسة حالة - عبير بوذينة; التجاني فاطمة الزهراء; سحنون اسراء سيرين (جامعة الوادي University of Eloued, 2025)
تهدف هذه الدراسة إلى إلقاء الضوء على أثر تطبيقات الذكاء الاصطناعي على آليات واستراتيجيات التسويق الإلكتروني، وذلك عن طريق توزيع 350 استبيان لدراسة حالة عينة من مستخدمي منصة Facebook Marketplace، والتي تعتبر واحدة من أبرز المنصات الرقمية في مجال التجارة الإلكترونية. وقد ظهرت هذه المنصة في السنوات الأخيرة كبيئة حيوية تعتمد على تقنيات الذكاء الاصطناعي لتحسين أداء أنشطتها التسويقية وتعزيز قدرتها التنافسية. ترمي الدراسة إلى تحليل كيفية توظيف الخوارزميات الذكية في دعم العمليات التسويقية، لا سيما من خلال أنظمة التوصية، وتحليل سلوك المستخدمين، والتحكم الآلي في الحملات الإعلانية، وهي تقنيات تسهم في تعزيز فعالية الحملات التسويقية، وتخصيص المحتوى الإعلاني بما يتناسب مع اهتمامات وتفضيلات المستخدمين، فضلاً عن تحسين تجربة المستخدم وزيادة معدلات التفاعل والشراء. This study aims to shed light on the impact of artificial intelligence applications on the mechanisms and strategies of electronic marketing through the distribution of 350 questionnaires to a sample of Facebook Marketplace platform users, which is considered one of the most prominent digital platforms in the field of e-commerce. This platform has emerged in recent years as a dynamic environment that relies on artificial intelligence technologies to improve the performance of its marketing activities and enhance its competitive edge. The study aims to analyze how smart algorithms are employed to support marketing processes, particularly through recommendation systems, user behavior analysis, and automated control of advertising campaigns. These technologies contribute to enhancing the effectiveness of marketing campaigns, customizing advertising content to align with users' interests and preferences, as well as improving user experience and increasing interaction and purchase rates.
ماستر
Keywords: طبيقات الذكاء الاصطناعي; التسويق الإلكتروني; خوارزميات، حملات إعلانية، فيسبوك.; AI applications; digital marketing; algorithms; advertising campaigns; Facebook.